2017
DOI: 10.1093/infdis/jix113
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Pathways That Predict Mortality in HIV-Infected Ugandans Initiating Antiretroviral Therapy

Abstract: The plasma kynurenine/tryptophan (KT) ratio, a marker of adaptive immune defects, strongly predicts mortality during treated human immunodeficiency virus (HIV) disease in Ugandans as compared to US-based populations. Here, the KT ratio and T-cell and plasma biomarkers of immune activation were measured among 535 HIV-infected Ugandans prior to ART initiation and at month 6 of viral suppression. The month 6 KT ratio (adjusted hazard ratio [aHR], 2.74), soluble CD14 level (aHR, 2.32), interleukin 6 level (aHR, 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 14 publications
1
43
1
1
Order By: Relevance
“…For example, among ART-suppressed HIV-infected individuals in North America, innate immune activation and inflammatory markers were much more strongly predictive of mortality than T cell activation (the opposite inference from the pre-ART era) [19, 20], presumably because most of the causes of death were non-infectious in etiology (e.g., cardiovascular, non-AIDS cancer, etc). Conversely, among ART-suppressed individuals in resource-limited settings, where infectious complications remain much more important causes of death [16, 17], T cell activation and pathways conferring adaptive immune defects are much stronger predictors of mortality [2123]. Thus, it would not be surprising if the final common immunologic pathways driving disease vary by end-organ complication.…”
Section: Persistent Immune Activation During Artmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among ART-suppressed HIV-infected individuals in North America, innate immune activation and inflammatory markers were much more strongly predictive of mortality than T cell activation (the opposite inference from the pre-ART era) [19, 20], presumably because most of the causes of death were non-infectious in etiology (e.g., cardiovascular, non-AIDS cancer, etc). Conversely, among ART-suppressed individuals in resource-limited settings, where infectious complications remain much more important causes of death [16, 17], T cell activation and pathways conferring adaptive immune defects are much stronger predictors of mortality [2123]. Thus, it would not be surprising if the final common immunologic pathways driving disease vary by end-organ complication.…”
Section: Persistent Immune Activation During Artmentioning
confidence: 99%
“…After more than two decades of research, it remains unclear whether CD38 and HLA-DR expression on CD4+ and CD8+ T cells are in and of themselves causally associated with disease or instead markers of exhaustion and/or dysfunction [32] in response to HIV, co-infection, or homeostasis- or activation-induced proliferation [33]. These markers continue to predict disease during ART-mediated viral suppression, but not as strongly as in the pre-ART era (when AIDS complications dominated) [19, 20, 22], and primarily in resource-limited settings [23]. …”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%
“…Importantly, these hallmarks of infection result in immune dysfunction that can often persist despite the initiation of antiretroviral therapy (ART). Immune dysfunction, as measured by type I IFN activity for example, is predictive of non-AIDS related morbidity and mortality in ART-treated individuals [ 3 6 ] and residual immune activation may account for the overall shorter life expectancy of HIV-infected subjects, particularly in those with incomplete immunologic restoration after ART initiation [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…(4) Other studies have also shown that elevated D-dimer levels in PLHIV both before and after ART initiation are correlated with greater risk of non-AIDS events and mortality in resource-rich (2,5) and resource limited settings among populations with advanced HIV disease. (3,6,7). PLHIV appear to be at higher risk for venous thrombotic events (8,9) likely due to activation of coagulation pathways resulting in a pro-coagulant states (10,11) which are associated with immunodeficiency and active viral replication.…”
Section: Introductionmentioning
confidence: 99%